The role of associations in reducing the emotional and financial impact on parents caring for children with duchenne muscular dystrophy : a cross-cultural study - Rodríguez, Alicia Aurora (2022)
Fil: Rodríguez, Alicia Aurora. Universidad de Deusto. Facultad de Ciencias de la Salud. Equipo de Investigación Neuro-e-Motion; España